Implementation of hots in mathematics: through the perspective of teachers - Sulaiman, Norliyah; Mohd Ayub, Ahmad Fauzi; Md. Yunus, Aida Suraya; Zulnaidi, Hutkemri; Abdul Manaf, Umi Kalthom (Innovare Academics Sciences, 2020)
Implementation of Higher Order Thinking Skills in Mathematics can improve student achievement. Teachers play a major role in understanding and inculcate thinking skills in the class. The aim of these studies to identified pedagogy, accessibility, and assessment in teaching and learning Mathematics based on HOTS in the classroom. These pilot studies were conducted using a qualitative approach in which interviews involved two mathematics teachers from two different categories of schools. The findings indicated that teachers understand and get an overview of HOTS. They implement it in the classroom although there are various constraints. Collaboration learning and exploration is an approach that teachers used to implement HOTS in the instructional. Teachers use any medium of tools as their instructional media. Examinations and tests were used to evaluate student achievement. Despite HOTS was evaluated through the problem discussion, exercises, and student's presentation during of teach and learn in class. Time constraints, source constraints, and readiness of students are seen as problems encountered in implementing HOTS. However, it is can be overcome depends on the teacher initiative. In conclusion, the implementation of HOTS will be more efficient if the teacher can generate student achievement through active learning with a variety of sources in many forms.